Figuras de la barbarie. Lugares y tiempo de la barbarie en Vico (pp. 151-162). Trad. de Josep Martínez. - Nuzzo, Enrico (Cuadernos sobre Vico, 2020)
CUADERNOS SOBRE VICO, 15-16 (2003). 441 págs. ISBN 1130-7498